Vitamins A, E, C, ?-carotene contents and MDA level of freshwater mussel, (Unio elongatulus eucirrus Bourguignat 1860) in the Karakaya Dam Lake - Sahin, Ayse Gul; Karatepe, Mustafa (Ege Univ, Fac Fisheries, 2022)
In this study, we aimed to determine the effect of domestic and agricultural discharge on the level of antioxidant vitamins A, E, C, beta-carotene and malondialdehyde (MDA, an indicator of oxidative stress) in the muscle tissue of freshwater mussel as known bioindicator (Unio elongatulus eucirrus). The freshwater mussels were collected from Arguvan (uncontaminated reference site) and Battalgazi (exposed to discharge site) in the Karakaya Dam Lake. In order to examine the effect of this discharge on freshwater mussel collected from these two different regions, antioxidant vitamins A, E, C, beta carotene and Malondialdehyde (MDA) levels were analyzed using High Performance Liquid Chromatography (HPLC). The comparison between groups from the different localities showed that concentrations of the vitamins A, E, C, beta-carotene and MDA were found statistically significant according to between the localities (p<0.05) The results showed that vitamins levels were higher and MDA levels were lower in the reference site.
Keywords: Karakaya Dam Lake; freshwater mussel; antioxidant vitamins; MDA; HPLC; bioindicator